Molecular mechanisms of heat shock factor 1 regulation - Kmiecik, Szymon; Mayer, Matthias P. (Trends in biochemical sciences, 2022)
To thrive and to fulfill their functions, cells need to maintain proteome homeostasis even in the face of adverse environmental conditions or radical restructuring of the proteome during differentiation. At the center of the regulation of proteome homeostasis is an ancient transcriptional mechanism, the so-called heat shock response (HSR), orchestrated in all eukaryotic cells by heat shock transcription factor 1 (Hsf1). As Hsf1 is implicated in aging and several pathologies like cancer and neurodegenerative disorders, understanding the regulation of Hsf1 could open novel therapeutic opportunities. In this review, we discuss the regulation of Hsf1’s transcriptional activity by multiple layers of control circuits involving Hsf1 synthesis and degradation, conformational rearrangements and post-translational modifications (PTMs), and molecular chaperones in negative feedback loops.